PERFORMANCE AND EMISSION CHARACTERISTICS OF CI ENGINE FUELLED WITH NON EDIBLE VEGETABLE OIL AND DIESEL BLENDS - T. ELANGO; T. SENTHILKUMAR (Journal of Engineering Science and Technology, 2011)
This study investigates performance and emission characteristics of a diesel engine which is fuelled with different blends of jatropha oil and diesel (10–50%). A single cylinder four stroke diesel engine was used for the experiments at various loads and speed of 1500 rpm. An AVL 5 gas analyzer and a smoke meter were used for the measurements of exhaust gas emissions. Engine performance (specific fuel consumption SFC, brake thermal efficiency, and exhaust gas temperature) and emissions (HC, CO, CO2, NOx and Smoke Opacity) were measured to evaluate and compute the behaviour of the diesel engine running on biodiesel. The results showed that the brake thermal efficiency of diesel is higher at all loads. Among the blends maximum brake thermal efficiency and minimum specific fuel consumption were found for blends upto 20% Jatropha oil. The specific fuel consumption of the blend having 20% Jatropha oil and 80% diesel (B20) was found to be comparable with the conventional diesel. The optimum blend is found to be B20 as the CO2 emissions were lesser than diesel while decrease in brake thermal efficiency is marginal.